1992
DOI: 10.1017/s0022112092001770
|View full text |Cite
|
Sign up to set email alerts
|

Velocity profile statistics in a turbulent boundary layer with slot-injected polymer

Abstract: The modification of a flat-plate turbulent boundary layer resulting from the injection of drag-reducing polymer solutions through a narrow inclined slot into the near-wall region of the flow has been studied. Two-component coincident laser-Doppler velocity profile measurements were taken with a free-stream velocity of 4.5 m/s with polymer injection, water injection, and no injection. Polyethylene oxide solutions at concentrations of 500 and 1025 w.p.p.m. were injected. These data are complemented by polymer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
37
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 19 publications
16
37
0
Order By: Relevance
“…The profile at x + --58 suggests that the effective size of the sublayer and buffer region has increased, thus shifting the profiles in y+. This behavior in the u' profiles is similar to that reported by Fontaine et al (1992) for drag reduced turbulent boundary layers with polymers. The profiles show a continual axial recovery beyond 232 wall units, with a complex spanwise recovery.…”
Section: The Attached Development and Recovery Region S8~supporting
confidence: 88%
See 2 more Smart Citations
“…The profile at x + --58 suggests that the effective size of the sublayer and buffer region has increased, thus shifting the profiles in y+. This behavior in the u' profiles is similar to that reported by Fontaine et al (1992) for drag reduced turbulent boundary layers with polymers. The profiles show a continual axial recovery beyond 232 wall units, with a complex spanwise recovery.…”
Section: The Attached Development and Recovery Region S8~supporting
confidence: 88%
“…The mean streamwise velocity profiles exhibit an upward shift of the log region when scaled with the reduced value of the Walker and Tiederman (1990) and Fontaine et al (1992) among others have shown a similar behavior in skin friction reduced profiles of flows with drag reducing polymers. The profiles at x + = 58 do not exhibit any noticeable distortions in their shape due to either the spike or the short separation zone behind the spike.…”
Section: The Attached Development and Recovery Region S8~mentioning
confidence: 53%
See 1 more Smart Citation
“…The flow rate of the injection Q i was set at 1.45 × 10 −2 l s −1 , which was comparable with the volume flow rate in the viscous sublayer and satisfies the limitation of Wu & Tulin (1972) as well as previous studies (e.g. Fontaine et al 1992;Hou et al 2008). We confirmed that turbulence statistics obtained by LDV measurements for turbulent boundary layer flow with the water injection were almost the same as those without the water injection (not shown in this paper).…”
supporting
confidence: 87%
“…Koskie & Tiederman (1991) investigated the drag reduction by the injection of polymer solutions for a turbulent boundary layer using LDV measurements. Fontaine, Petrie & Brungart (1992) performed the LDV and laser-induced fluorescence (LIF) measurements and found that the bursting process was suppressed by injection of polymer solutions into the near-wall region of a turbulent boundary layer. White, Somandepalli & Mungal (2004) and Hou, Somandepalli & Mungal (2008) clarified the effects of polymer additives on the turbulent boundary layer using PIV measurements.…”
mentioning
confidence: 99%